2015
DOI: 10.1002/lno.10138
|View full text |Cite
|
Sign up to set email alerts
|

Resource supply alone explains the variability of marine phytoplankton size structure

Abstract: Due to the covariation between temperature and resource availability in the surface ocean, a correct assessment of resource supply is crucial to determine if temperature has a direct effect on phytoplankton size structure. To remove the effect of resources, L opez-Urrutia and Mor an analyzed data subsets with narrow ranges of variation in Chlorophyll a (Chl a) concentration and found that temperature is correlated with Chl a partitioning among size classes, from which they concluded that temperature is an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
(51 reference statements)
9
27
1
Order By: Relevance
“…This may be due to the prevailing influence of physical factors in the phytoplankton nutrient uptake. Our results agree with previous studies in marine systems where changes in resource supply alone have been demonstrated as sufficient to explain the variability of phytoplankton size structure (Marañón et al., ). In phytoplankton assemblages, smaller sizes are favoured at low nutrient availability due to the higher surface:volume ratio or lower resource requirements, whereas large algae are often (but see Jensen, Jeppesen, Olrik, & Kristensen, ) better competitors at high concentrations (Guidi et al., ; Litchman & Klausmeier, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This may be due to the prevailing influence of physical factors in the phytoplankton nutrient uptake. Our results agree with previous studies in marine systems where changes in resource supply alone have been demonstrated as sufficient to explain the variability of phytoplankton size structure (Marañón et al., ). In phytoplankton assemblages, smaller sizes are favoured at low nutrient availability due to the higher surface:volume ratio or lower resource requirements, whereas large algae are often (but see Jensen, Jeppesen, Olrik, & Kristensen, ) better competitors at high concentrations (Guidi et al., ; Litchman & Klausmeier, ).…”
Section: Discussionsupporting
confidence: 93%
“…pulses of reproduction due to increased food availability, resulting in dominance of small individuals and low size diversity) (García‐Comas et al., ). Furthermore, resource availability may have a bigger effect on phytoplankton than in other trophic groups (Marañón, Cermeño, Latasa, & Tadonléké, ; Quintana et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The data compilation of Marañón et al (2012) was re-analysed by López-Urrutia & Morán (2015) who found a nutrient-independent temperature effect: the proportion of picoplankton increased with temperature in the low-productivity subset ([chlorophyll a] <1 μg l −1 ) while the proportion of microplankton decreased with temperature in the high-productivity subset ([chlorophyll a] >2 μg l −1 ). However, in their reply Marañón et al (2015) showed that size was also correlated with resource supply within the subsets defined by chlorophyll a concentrations.…”
Section: Global Trends In the Ocean (1) Size Variation Assessed mentioning
confidence: 99%
“…While many authors claim that the size-temperature trend is dominantly driven by a negative temperature-nutrient correlation (e.g. Marañón et al, 2015) others claim that there is an additional, direct temperature effect (e.g. López-Urrutia & Morán, (2015) strong limitation (N:P = 40:1); 5d, Peter & Sommer (2015) strong limitation (N:P = 4:1); 6a, Sommer et al (2015), low CO 2 ; 6b, Sommer et al (2015), high CO 2 .…”
Section: Direct Versus Indirect Mechanisms Of Size Changementioning
confidence: 99%
“…Which relationship dominates in seas? The debate has continued for decades (e.g., Morán et al ; Hilligsøe et al ; Marañón et al , ; López‐Urrutia and Morán ). Note too, that there are several examples which do not follow these two classic relationships: some studies identify no effect of increasing resource availability on body size (e.g., Sprules and Munawar ; Cavender‐Bares et al ), and other studies show increasing or unchanging body sizes with increasing temperature (e.g., Rüger and Sommer ; Adams et al ).…”
mentioning
confidence: 99%